Response of PIWI grapevine cultivars to downy mildew in highland region of southern Brazil - Zanghelini J.A.* (2019)
© 2019, Koninklijke Nederlandse Planteziektenkundige Vereniging.Downy mildew (DM) caused by Plasmopara viticola is a major grapevine disease in southern Brazil. Control of DM requires frequent fungicide treatments or the use of resistant cultivars. The pyramiding of previously identified resistance loci allows the selection of genotypes with combined resistance loci in order to build up sustainable resistance. The objective of this study was to evaluate the resistance response of PIWI cultivars Felicia, Brönner, and Calardis Blanc, containing Rpv3.1, Rpv10, and Rpv3.1 + Rpv3.2 loci, respectively, and two advanced breeding selections (ABS) containing the Rpv1 + Rpv3.1 pyramided, to the development of DM temporal dynamics. The experiment was conducted at an experimental vineyard in the highland of southern Brazil, during the 2016/2017 and 2017/2018 growing seasons. The genotype UFSC-2012-1-24 without resistance loci was used as susceptible control. DM incidence and severity were assessed biweekly from the first symptoms appearance until harvest. The cultivars and ABS were compared based on the following DM epidemiological parameters: a) beginning of symptoms appearance (BSA); b) maximum disease incidence and severity (Imax, Smax); c) time to reach maximum disease incidence/severity (TRMDI and TRMDS); and d) areas under incidence and severity disease progress curves (AUIDPC and AUSDPC). In general, there were significant differences in the estimated parameters depending on the genotype. The principal epidemiological variables that differentiated the PIWI cultivars were Smax and AUSDPC. The PIWI cultivars showed significantly lower Smax and AUSDPC of DM in comparison to the susceptible control in both 2016/2017 and 2017/2018 growing seasons. There were also significant differences between the cultivars for AUIDPC and AUSDPC in both growing seasons. Felicia cultivar showed the highest AUIDPC and AUSDPC in the 2016/2017 growing season. Surprisingly, in the growing seasons 2017/2018, Calardis Blanc displayed an increase in disease incidence and severity, showing a similar AUIDPC and AUSDPC to Felicia cultivar. In general, Bronner cultivar was the most resistant to DM. The ABS showed the lowest value of Imax, Smax, AUIDPC and AUSDPC, suggesting the effectiveness of the Rpv1 + Rpv3.1 pyramiding. The PIWI cultivars showed partial resistance to DM and are potential options for reducing fungicide use. The results showed that the pyramiding of resistance loci is fundamental to increase the genetic resistance to DM.